2009
DOI: 10.1007/s00493-009-2356-y
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings and Ramsey numbers of sparse κ-uniform hypergraphs

Abstract: Chvátal, Rödl, Szemerédi and Trotter [3] proved that the Ramsey numbers of graphs of bounded maximum degree are linear in their order. In [6, 23] the same result was proved for 3-uniform hypergraphs. Here we extend this result to k-uniform hypergraphs for any integer k ≥ 3. As in the 3-uniform case, the main new tool which we prove and use is an embedding lemma for k-uniform hypergraphs of bounded maximum degree into suitable k-uniform 'quasi-random' hypergraphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
126
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(128 citation statements)
references
References 26 publications
2
126
0
Order By: Relevance
“…The strategy for the k-uniform case in [3] is similar to the one used here, but several additional problems arise.…”
Section: Embedding Graphs and Hypergraphsmentioning
confidence: 96%
See 2 more Smart Citations
“…The strategy for the k-uniform case in [3] is similar to the one used here, but several additional problems arise.…”
Section: Embedding Graphs and Hypergraphsmentioning
confidence: 96%
“…More precisely, they showed that for all ε, Δ, k > 0 there is a constant C such that R(H ) C|H | 1+ε if H is k-uniform and has maximum degree at most Δ. In a sequel [3] to this paper, we generalised Theorem 1 to k-uniform hypergraphs of bounded degree for arbitrary k. This was also done independently by Ishigami [12]. Another related result is that of Haxell et al [9,10], who asymptotically determined the Ramsey numbers of 3-uniform tight and loose cycles.…”
Section: Ramsey Numbersmentioning
confidence: 97%
See 1 more Smart Citation
“…Since the first proof of the sparse graph Ramsey theorem used Szemerédi's regularity lemma, it was therefore natural to expect that, given the recent advances in developing a hypergraph regularity method [14,25,23], linear bounds might as well be provable for hypergraphs. Such a program was indeed recently pursued by several authors (Cooley, Fountoulakis, Kühn, and Osthus [6,7]; Nagle, Olsen, Rödl, and Schacht [22]; Ishigami [18]), with the result that we now have the following theorem:…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, for regular k-complexes we have a Counting Lemma (see [3,5,6,7,8]), which gives the approximate number of copies of any small fixed k-complex within a regular k-complex, as well an Extension Lemma [2], an Embedding Lemma [2] and (under some additional conditions) a Blow-up Lemma [4], each of which functions similarly as in the graph case.…”
Section: Regular Complexesmentioning
confidence: 99%